REKONSTRUKSI HUKUM ATAS RUU TINDAK PIDANA PENYELENGGARAAN PERADILAN: UPAYA PENINGKATAN KINERJA KOMISI YUDISIAL DAN MAHKAMAH AGUNG - Junior B. Gregorius (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This article was written with the aim of analyzing how the legal reconstruction of the Judicial Administration-Contempt of Court Crime Bill ("hereinafter refered to the “CoC Bill") is a way for the Judicial Commission to improve its performance and relations with the Supreme Court. One side of the judge (IKAHI) hopes that this bill will soon be passed by the DPR. On the other hand, many groups of people reject the draft because it is considered very excessive and has the potential to threaten the freedom of citizens. By using normative legal research methods and legislative approaches as well as thinking about legal effectiveness according to Lawrence M. Friedman as an analytical tool, this article finds that the legal reconstruction that must be carried out by the Judicial Commission is: first, regarding the definition of criminal acts by justice administrators (contempt of court) second, regarding the principles of criminal law, third, conflicts with criminal procedural law, fourth, regarding articles that overlap with the Criminal Code, fifth, regarding high criminal threats, sixth, regarding the evidentiary system and seventh, theoretical reflection. The results of the legal reconstruction by the Judicial Commission were then discussed with various law enforcement parties, legal observers, academics, practitioners and the public. The final result of the reconstruction and discussion is that the Draft is submitted back to the DPR.